Integrated Model of Peace Education Based on Contextual Islamic Washatiyah at Nurul Islam, Islamic Boarding School Jember - Asnawan, Asnawan (IAIN Ponorogo, 2021)
Abstrak: Nurul Islam Islamic Boarding School since its establishment has set itself as a peace boarding school having moderate character. When radicalism, extremism, and terrorism threaten world peace, the schools consistently campaign for peace. Therefore, the research focuses on peace education planning, implementation, and implication on students' behavior and attitude in Nurul Islam Islamic Boarding School Jember to find out a planning, implementation, and implication model of peace education. The research is a qualitative study using a multiple case study approach. The informants were chosen using a purposive sampling technique. The findings of the research are: first, peace education planning in Nurul Islam Islamic Boarding School Jember refers to vision, mission, institutional philosophy, Islam washatiyah (moderate), started with the need analysis of times, society, and students and by considering the suggestion of education users formulated by the educational institution. Second, peace education implementation employs an adaptation of religious text material using moderation approach, Islamic method and universal method, a website supporting media containing digital washatiyah literacy and digital Sufism literacy implemented informal institution integrated with ahl al-sunnah wa al-jamaâ€™ah teaching through class-based inter curricular activities and intensive and doctrinal extracurricular activities. Third, the peace education implication in Islamic boarding school builds students' polite and tolerant behavior, moderate and contextual perspective, Sufistic behavior, positive image for the local, national and regional society and supports Islamic boarding school continuous transformation. The formal finding of the research is an integrative peace education model based on contextual Islam washatiyah.Ø§Ù„Ù…Ù„Ø®Øµ: Ø£Ø¹Ù„Ù† Ù…Ø¹Ù‡Ø¯ Ù†ÙˆØ± Ø§Ù„Ø¥Ø³Ù„Ø§Ù… Ù…Ù†Ø° Ø¨Ø¯Ø§ÙŠØ© Ù†Ø´Ø£ØªÙ‡Ù…Ø§ Ø¨Ø£Ù†Ù‡Ù…Ø§ Ù…Ø¹Ù‡Ø¯ Ø§Ù„Ø³Ù„Ø§Ù… Ø§Ù„Ø°ÙŠ Ù„Ù‡Ø§ Ø®ØµÙŠØ© ÙƒÙ…Ø¹Ù‡Ø¯ Ø¨Ø§ØªØ¬Ø§Ù‡ Ù…Ø¹ØªØ¯Ù„ ÙˆÙ…Ø¹ØªÙ…Ø¯ Ø¹Ù„Ù‰ ØªÙ‚Ø§Ù„ÙŠØ¯ Ø§Ù„Ø°ÙƒØ± ÙˆØ§Ù„Ù…Ù†Ø§Ù‚Ø¨. ÙˆÙÙŠ Ø§Ù„ÙˆÙ‚Øª Ø§Ù„Ø°ÙŠ ÙŠØªØ¹Ø±Ø¶ ÙÙŠÙ‡ Ø§Ù„Ø¹Ø§Ù„Ù… Ù„Ù„ØªÙ‡Ø¯ÙŠØ¯ Ù…Ù† Ø§Ù„ØªØ·Ø±Ù ÙˆØ§Ù„Ø§Ù‚ØªÙƒØ§Ø¡ ÙˆØ§Ù„Ø¥Ø±Ù‡Ø§Ø¨ØŒ ÙŠØ¸Ù„ Ø°Ù„Ùƒ Ø§Ù„Ù…Ø¹Ù‡Ø¯ Ù†Ø§Ø·Ù‚Ø§ Ø±Ø¦ÙŠØ³ÙŠØ§ ÙÙŠ ØÙ…Ù„Ø© Ø§Ù„Ø³Ù„Ø§Ù…. Ù„Ø°Ù„ÙƒØŒ ÙØ¥Ù† Ø§Ø³ØªÙƒØ´Ø§Ù Ù‡Ø°Ø§ Ø§Ù„Ø¨ØØ« ÙŠØªØ±ÙƒØ² Ø¹Ù„Ù‰ ØªØ®Ø·ÙŠØ· ÙˆØªÙ†ÙÙŠØ° ÙˆØ¢Ø«Ø§Ø± Ù…ØªØ±ØªØ¨Ø© Ù…Ù† ØªØ±Ø¨ÙŠØ© Ø§Ù„Ø³Ù„Ø§Ù… Ø¹Ù„Ù‰ Ù…ÙˆØ§Ù‚Ù ÙˆØ³Ù„ÙˆÙƒÙŠØ§Øª Ø§Ù„Ø·Ù„Ø§Ø¨ ÙÙŠ Ù…Ø¹Ù‡Ø¯ Ù†ÙˆØ± Ø§Ù„Ø¥Ø³Ù„Ø§Ù… Ø¬Ù…Ø¨Ø± Ø¨Ù‡Ø¯Ù Ø¥ÙŠØ¬Ø§Ø¯ Ù†Ù…ÙˆØ°Ø¬ ØªØ®Ø·ÙŠØ· Ø§Ù„ØªÙ†ÙÙŠØ° ÙˆØ§Ù„Ø¢Ø«Ø§Ø± Ø§Ù„Ù…ØªØ±ØªØ¨Ø© Ù…Ù† ØªØ±Ø¨ÙŠØ© Ø§Ù„Ø³Ù„Ø§Ù…. Ø§Ø³ØªØ®Ø¯Ù… Ù‡Ø°Ø§ Ø§Ù„Ø¨ØØ« Ù…Ù†Ù‡Ø¬ Ø§Ù„Ø¨ØØ« Ø§Ù„ÙƒÙŠÙÙŠ Ø¨Ù†ÙˆØ¹ Ø¯Ø±Ø§Ø³Ø© Ø§Ù„ØØ§Ù„Ø© Ù…Ø¹ ØªØµÙ…ÙŠÙ… Ø¯Ø±Ø§Ø³Ø© Ù…ØªØ¹Ø¯Ø¯ Ø§Ù„ØØ§Ù„Ø§Øª.Â ØªÙ… Ø§Ø®ØªÙŠØ§Ø± Ø§Ù„Ù…Ø®Ø¨Ø±ÙŠÙ† Ù…Ù† Ø®Ù„Ø§Ù„ ØªÙ‚Ù†ÙŠØ§Øª Ø£Ø®Ø° Ø§Ù„Ø¹ÙŠÙ†Ø§Øª Ø§Ù„Ù…ØØ¯Ø¯Ø©ØŒ ÙˆØ¬Ù…Ø¹ Ø§Ù„Ø¨ÙŠØ§Ù†Ø§Øª Ø¨Ø§Ø³ØªØ®Ø¯Ø§Ù… Ø§Ù„Ù…Ù‚Ø§Ø¨Ù„Ø© ØºÙŠØ± Ø§Ù„Ù…Ù†Ø¸Ù…Ø©ØŒ ÙˆØ§Ù„Ù…Ù„Ø§ØØ¸Ø© ØºÙŠØ± Ø§Ù„Ù…Ø´Ø§Ø±ÙƒØ© ÙˆØ§Ù„ÙˆØ«Ø§Ø¦Ù‚. Ø§Ø³ØªØ®Ø¯Ù… Ø§Ù„Ø¨Ø§ØØ« ØªØÙ„ÙŠÙ„ Ø§Ù„Ø¨ÙŠØ§Ù†Ø§Øª Ø¨Ù†Ù…ÙˆØ°Ø¬ Ù…ÙŠÙ„Ø² ÙˆÙ‡ÙˆØ¨Ø±Ù…Ø§Ù† Ø§Ù„Ø°ÙŠ Ø·Ø¨Ù‚ Ø¹Ù„Ù‰ Ù…Ø±ØÙ„ØªÙŠÙ†: Ù¡. ØªØÙ„ÙŠÙ„ Ø¨ÙŠØ§Ù†Ø§Øª Ø§Ù„ØØ§Ù„Ø§Øª Ø§Ù„ÙØ±Ø¯ÙŠØ©ØŒ Ùˆ Ù¢. ØªØÙ„ÙŠÙ„ Ø§Ù„Ø¨ÙŠØ§Ù†Ø§Øª Ø¹Ø¨Ø± Ø§Ù„ØØ§Ù„Ø§Øª. ÙˆØªÙ… Ø§Ù„ØªØÙ‚Ù‚ Ù…Ù† ØµØØ© Ø§Ù„Ø¨ÙŠØ§Ù†Ø§Øª Ù…Ù† Ø®Ù„Ø§Ù„ ØªØ«Ù„ÙŠØ« Ø§Ù„Ø·Ø±ÙŠÙ‚Ø©ØŒ ÙˆØ§Ù„Ø§Ø¹ØªÙ…Ø§Ø¯ÙŠØ©ØŒ ÙˆØ§Ù„ØªØ£ÙƒØ¯ÙŠØ©.Ø£Ø¸Ù‡Ø±Øª Ù†ØªØ§Ø¦Ø¬ Ù‡Ø°Ø§ Ø§Ù„Ø¨ØØ« Ù…Ø§ ÙŠÙ„ÙŠ: Ø£ÙˆÙ„Ø§ØŒ ØªØ®Ø·ÙŠØ· ØªØ±Ø¨ÙŠØ© Ø§Ù„Ø³Ù„Ø§Ù… ÙÙŠ Ù…Ø¹Ù‡Ø¯ Ù†ÙˆØ± Ø§Ù„Ø¥Ø³Ù„Ø§Ù… Ù‡Ùˆ Ø§Ù„ØªØ®Ø·ÙŠØ· Ø§Ù„Ù‚Ø§Ø¦Ù… Ø¹Ù„Ù‰ Ø§Ù„Ø±Ø¤ÙŠØ© ÙˆØ§Ù„Ø±Ø³Ø§Ù„Ø© ÙˆØ§Ù„Ø§Ù‡ØªÙ…Ø§Ù… Ø¨ÙÙ„Ø³ÙØ© Ø§Ù„Ù…Ø¤Ø³Ø³Ø© ÙˆØ¨Ù…Ø¨Ø¯Ø£ Ø§Ù„Ø¥Ø³Ù„Ø§Ù… Ø§Ù„ÙˆØ³Ø·ÙŠ (Ø§Ù„Ù…Ø¹ØªØ¯Ù„Ø©)ØŒ ÙŠØ³Ø¨Ù‚Ù‡Ø§ ØªØÙ„ÙŠÙ„ Ø§ØØªÙŠØ§Ø¬Ø§Øª Ø§Ù„Ø¹ØµØ± ÙˆØ§Ù„Ù…Ø¬ØªÙ…Ø¹ ÙˆØ§Ù„Ø·Ù„Ø§Ø¨ ÙˆØ§Ù„Ø§Ù‡ØªÙ…Ø§Ù… Ø¨Ù…Ø¯Ø®Ù„Ø§Øª Ù…Ø³ØªØ®Ø¯Ù…ÙŠ Ø§Ù„Ø®Ø¯Ù…Ø© Ø§Ù„ØªØ¹Ù„ÙŠÙ…ÙŠØ© Ø§Ù„ØªÙŠ ØªØµÙˆØºÙ‡Ø§ Ø§Ù„Ù…Ø¤Ø³Ø³Ø§Øª Ø§Ù„ØªØ¹Ù„ÙŠÙ…ÙŠØ©. Ø«Ø§Ù†ÙŠØ§Ù‹ØŒ ØªÙ†ÙÙŠØ° ØªØ±Ø¨ÙŠØ© Ø§Ù„Ø³Ù„Ø§Ù… Ø§Ù„Ø°ÙŠ ÙŠØªØ±ÙˆØ Ù…Ø¹ Ù…Ø§Ø¯Ø© Ù…Ù† Ø§Ù„Ù†ØµÙˆØµ Ø§Ù„Ø¯ÙŠÙ†ÙŠØ© Ø¨Ù…Ù†Ù‡Ø¬ Ø§Ù„Ø§Ø¹ØªØ¯Ø§Ù„ØŒ Ø¨Ø§Ø³ØªØ®Ø¯Ø§Ù… Ø§Ù„Ø£Ø³Ù„ÙˆØ¨ Ø§Ù„Ø¥Ø³Ù„Ø§Ù…ÙŠ ÙˆØ§Ù„Ø£Ø³Ù„ÙˆØ¨ Ø§Ù„Ø¹Ø§Ù„Ù…ÙŠØŒ ÙˆØ¯Ø¹Ù… Ø§Ù„Ù…ÙˆÙ‚Ø¹ Ø§Ù„Ø¥Ø¹Ù„Ø§Ù…ÙŠ Ø¨Ø§Ù„Ù…ØØªÙˆÙ‰ Ø§Ù„Ø±Ù‚Ù…ÙŠ ÙˆÙ…ØÙˆ Ø§Ù„Ø£Ù…ÙŠØ© Ø§Ù„ØµÙˆÙÙŠØ© Ø§Ù„Ø±Ù‚Ù…ÙŠØ© Ø§Ù„Ù…Ù†ÙØ°Ø© ÙÙŠ Ø§Ù„Ù…Ø¤Ø³Ø³Ø§Øª Ø§Ù„Ø±Ø³Ù…ÙŠØ© Ù…Ø¹ Ù†Ù…Ø· Ù…Ù† Ø§Ù„ØªÙƒØ§Ù…Ù„ Ø¨ÙŠÙ† ØªØ¹Ø§Ù„ÙŠÙ… Ø£Ù‡Ù„ Ø§Ù„Ø³Ù†Ø© ÙˆØ§Ù„Ø¬Ù…Ø§Ø¹Ø© Ø³ÙˆØ§Ø¡ ÙƒØ§Ù† Ù…Ù† Ø®Ù„Ø§Ù„ Ø§Ù„Ù…Ù†Ø§Ù‡Ø¬ Ø§Ù„Ø¯Ø±Ø§Ø³ÙŠØ© Ø§Ù„Ù‚Ø§Ø¦Ù…Ø© Ø¹Ù„Ù‰ Ø§Ù„ØµÙÙŠØ© ÙˆØ§Ù„Ù„Ø§ØµÙÙŠØ© Ù…ÙƒØ«ÙØ§ Ø£Ùˆ Ù…Ø°Ù‡Ø¨ÙŠØ§. Ø«Ø§Ù„Ø«Ø§Ù‹ØŒ ØªÙØ´ÙƒÙ„ Ø§Ù„Ø¢Ø«Ø§Ø± Ø§Ù„Ù…ØªØ±ØªØ¨Ø© Ù…Ù† ØªØ±Ø¨ÙŠØ© Ø§Ù„Ø³Ù„Ø§Ù… ÙÙŠ Ø§Ù„Ù…Ø¹Ù‡Ø¯ Ù…ÙˆÙ‚ÙØ§Ù‹ Ù…Ù‡Ø°Ø¨Ø§Ù‹ ÙˆÙ…ØªØÙ…Ø³Ø§ØŒ ÙˆØªØ´ÙƒÙŠÙ„ ÙˆØ¬Ù‡Ø© Ø§Ù„Ù†Ø¸Ø± Ø§Ù„Ù…Ø¹ØªØ¯Ù„Ø© Ø§Ù„Ø³ÙŠØ§Ù‚ÙŠØ©ØŒ ÙˆØªØ´ÙƒÙŠÙ„ Ù…ÙˆÙ‚Ù Ø§Ù„ØªØµÙˆÙ Ù„Ø¯Ù‰ Ø§Ù„Ø·Ù„Ø§Ø¨ØŒ ÙˆØªØ´ÙƒÙŠÙ„ ØµÙˆØ±Ø© Ø¥ÙŠØ¬Ø§Ø¨ÙŠØ© Ù„Ù„Ù…Ø¬ØªÙ…Ø¹Ø§Øª Ø§Ù„Ù…ØÙ„ÙŠØ© ÙˆØ§Ù„ÙˆØ·Ù†ÙŠØ© ÙˆØ§Ù„Ø¥Ù‚Ù„ÙŠÙ…ÙŠØ©ØŒ ÙˆØªØ´Ø¬Ø¹ Ø§Ù„ØªØÙˆÙ„ Ø§Ù„Ù…Ø¤Ø³Ø³ÙŠ Ù„Ù„Ù…Ø¹Ù‡Ø¯ Ø¨Ø·Ø±ÙŠÙ‚Ø© Ù…Ø³ØªØ¯Ø§Ù…Ø©. Ø§Ù„Ù†ØªØ§Ø¦Ø¬ Ø§Ù„Ø±Ø³Ù…ÙŠØ© ÙÙŠ Ù‡Ø°Ø§ Ø§Ù„Ø¨ØØ« Ù‡ÙŠ Ù†Ù…Ø§Ø°Ø¬ ØªØ±Ø¨ÙŠØ© Ø§Ù„Ø³Ù„Ø§Ù… Ø§Ù„ØªÙƒØ§Ù…Ù„ÙŠØ© Ø§Ù„Ù‚Ø§Ø¦Ù…Ø© Ø¹Ù„Ù‰ Ø§Ù„Ø¥Ø³Ù„Ø§Ù… Ø§Ù„ÙˆØ·Ù†ÙŠ Ø§Ù„Ø³ÙŠØ§Ù‚ÙŠ.